IL‐17‐producing CD4+ T cells contribute to the loss of B‐cell tolerance in experimental autoimmune myasthenia gravis. Issue 5 (20th March 2015) - Schaffert, Hanne; Pelz, Andreas; Saxena, Abhishek; Losen, Mario; Meisel, Andreas; Thiel, Andreas; Kohler, Siegfried
<x xml:space="preserve">Abstract</x> The role of Th17 cells in the pathogenesis of autoantibody‐mediated diseases is unclear. Here, we assessed the contribution of Th17 cells to the pathogenesis of experimental autoimmune myasthenia gravis (EAMG), which is induced by repetitive immunizations with Torpedo californica acetylcholine receptor (tAChR). We show that a significant fraction of tAChR‐specific CD4+ T cells is producing IL‐17. IL‐17ko mice developed fewer or no EAMG symptoms, although the frequencies of tAChR‐specific CD4+ T cells secreting IL‐2, IFN‐γ, or IL‐21, and the percentage of FoxP3+ Treg cells were similar to WT mice. Even though the total anti‐tAChR antibody levels were equal, the complement fixating IgG2b subtype was reduced in IL‐17ko as compared to WT mice. Most importantly, pathogenic anti‐murine AChR antibodies were significantly lower in IL‐17ko mice. Furthermore, we confirmed the role of Th17 cells in EAMG pathogenesis by the reconstitution of TCR β/δko mice with WT or IL‐17ko CD4+ T cells. In conclusion, we show that the level of IgG2b and the loss of B‐cell tolerance, which results in pathogenic anti‐murine AChR‐specific antibodies, are dependent on IL‐17 production by CD4+ T cells. Thus, we describe here for the first time how Th17 cells are involved in the induction of classical antibody‐mediated autoimmunity.